First description of the male of Diaea mikhailovi (Araneae: Thomisidae) - Guo, Chen-Hui; Zhang, Feng (Zootaxa, 2014)
The genus Diaea Thorell, 1869 contains 75 known species with the type species D. dorsata (Fabricius, 1777). It is distributed worldwide, and about half of the species currently assigned to this genus are found in Australasia (Platnick 2014). Four Diaea species have been recorded from China, D. subdola O. P.-Cambridge, 1885, D. suspiciosa O. P.-Cambridge, 1885, D. mikhailovi Zhang, Song & Zhu, 2004 and D. simplex Xu, Han & Li, 2008 (Li & Wang 2014; Platnick 2014).